Clinical profile and surgical outcome of abdominal hydatid cyst at a university hospital in Nepal - Maharjan, Shanta Bir; Paudyal, Sanjaya; Shah, Sailendra; Dahal, Romi; Shah, Jay Narayan (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Hydatid cyst is caused by the tapeworm. It is common in sheep and cattle rearing communities. Liver is the most common affected organ. There are various methods of surgical approaches for hydatid cyst.Methods: This was a retrospective descriptive study of patients operated for intra-abdominal hydatid cysts from July 2012 to June 2018 at Patan Hospital, Patan Academy of Health Sciences, Nepal. Ethical approval from institutional review committee was obtained. Patient files with incomplete data were excluded. Variables analyzed were, age, gender, site and numbers of cyst, methods of surgery, complications and mortality. Data were descriptively analyzed.Results: There were 19 patients of abdominal hydatid cysts who underwent surgery during the study period. Five records files could not be accessed and were excluded. In remaining 14, male were 6 (42.85%), female 8 (57.15%), mean age 39.57±17.35 years (14-70), cyst size 11±4.22 cm (5-21), complain of abdominal pain in 10 (71%). Open surgery for liver cyst was done in 11 and laparoscopic in one, and open splenectomy for two splenic cysts. One patient developed superficial wound infection. Four had cystobiliary communication of which one underwent ERCP. Post ERCP patient developed acute severe pancreatitis and expired.Mean hospital was 8.57±2.24 days (6-14).Conclusions: Liver was the main organ involved, abdominal pain and lump were main presenting complaints. Surgery had successful outcome. Open surgery was the mainstay of treatment.